2002
DOI: 10.1097/00007890-200210150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Oral efficacy of the new immunomodulator FTY720 in cynomolgus monkey kidney allotransplantation, given alone or in combination with cyclosporine or RAD

Abstract: FTY720 is an effective immunosuppressant in prevention of acute kidney allograft rejection in cynomolgus monkeys and synergizes with cyclosporine and/or RAD in yielding rejection-free allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…ϩ T cells and 30% of CD8 T cells were refractory to depletion by the drug (24). The current view is that these cells represent long-lived effector memory T cells because in contrast to naive and central memory T cells they lack the lymph node homing receptors CCR7 and CD62L and reside in nonlymphoid tissues (33)(34)(35).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ϩ T cells and 30% of CD8 T cells were refractory to depletion by the drug (24). The current view is that these cells represent long-lived effector memory T cells because in contrast to naive and central memory T cells they lack the lymph node homing receptors CCR7 and CD62L and reside in nonlymphoid tissues (33)(34)(35).…”
Section: Discussionmentioning
confidence: 98%
“…However, multiple studies have demonstrated that the depletion of lymphocytes from the circulation is not complete, suggesting the presence of a T cell subpopulation that is resistant to FTY720 (23,24). Because little is known about the effect of FTY720 on the sequestration of CD4 ϩ /CD25 ϩ T-regulatory cells, the distribution of this lymphocyte subpopulation in blood and spleen after treatment with FTY720 was investigated.…”
Section: Increased Numbers Of Cd4mentioning
confidence: 99%
“…therapy; migration; I cell 2-AMINO-2-[2-(4-OCTYLPHENYL)ETHYL]-1,3-PROPANEDIOL HYDROCHLO-RIDE (FTY720) is a chemical derivative of myriocin (thermozymocidin), a substance found in the fungi Myriococcum albomyces and Isaria sinclairii (1,2,5,6). FTY720 is a potent immunomodulator that has been shown to prevent graft rejection in various animal allotransplantation models (23,24), autoimmune disease animal models (11,16,20), and viral infection animal models (17,21). Good synergy with cyclosporine and sirolimus has been reported (3,28,30).…”
Section: Cd45rbmentioning
confidence: 99%
“…In nohuman primates treated with FTY720 for over 100 days, however, ϳ10% of peripheral blood CD4 ϩ T cells were refractory to depletion by FTY720 (23). It is likely that these cells represent long-lived T EM cells.…”
Section: Cd45rbmentioning
confidence: 99%
“…Several studies demonstrated the reduced inflammatory cellular infiltration of allogeneic grafts under the cover of FTY720 treatment (8,9). FTY720 synergistically acts in combination with calcineurin inhibitors or rapamycin, preventing more efficiently acute rejection and development of chronic graft dysfunction (10,11). Based on these data, the beneficial effects of FTY720 in combination with several immunosuppressive protocols are now under clinical investigation.…”
Section: Introductionmentioning
confidence: 99%